Analisis Backlog Perumahan di Kota Manado (Housing Backlog Analysis in Manado City) - Gracia Marjorie Tindas; Grace A. J. Rumagit; Sherly G. Jocom (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to identify the availability of houses and the distribution of houses in Manado City and analyze the housing backlog and the direction of housing development policies in Manado City in 2014-2021. This research was conducted from March 2022 to May 2022. The data used in this study were primary data and secondary data. Primary data in the form of interviews and direct observations in the field, while secondary data BPS North Sulawesi Province and the Department of Housing and Settlements Manado City. The data analysis method uses Overlay Analysis and Housing Backlog Calculation. The research results showed that the availability of houses in Manado City in 2014-2021 increased by 15,098 housing units, the three sub-districts with the highest number of houses were Mapanget District (21,693 housing units), Malalayang District (18,341 housing units) and Wanea District (13,261). Overall, the housing backlog from 2014-2021 showed a decline in 10,380 housing units (29,827 housing units to 19,447 housing units). Policies and programs implemented by the government are still not optimal in achieving their goals.